Design Of A Vector Teaching Module For High School In The Independent Curriculum Based On Problem-Based Learning Integration Numeracy Ability - Panuli, Ari; Nandang, Nandang; Mulyana, Diki; Lestari, Wiwit Damayanti (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
The purpose of this research was to design a high school vector learning module within the Independent Curriculum based on Problem-Based Learning (PBL) integrating numeracy skills with valid and practical criteria. This research was R&D (Research and Development), and the research model used was ADDIE (analysis, design, development, implementation, and evaluation). Data collection used validation instruments and questionnaires. The module was validated by five expert validators, and its practicality was piloted by two teachers and 15 students. Based on the research results, the PBL-based learning module design integrating numeracy skills was declared highly valid with an average validity percentage of 76% and met the criteria for highly practical with an average practicality percentage of 89%. The research concluded that the PBL-based learning module design met the criteria for highly valid and practical, making it suitable for use in the 10th-grade high school mathematics learning process for vectors.